Advances in Artificial Systems for Power Engineering II - Hu, Zhengbing; Wang, Bo; Petoukhov, Sergey; He, Matthew (Lecture Notes on Data Engineering and Communications Technologies, 2022)
XI, 220 p. 93 illus., 64 illus. in color.